Implementasi Pengukuran, Penilaian, dan Evaluasi untuk Meningkatkan Kualitas Pembelajaran PAI SMA MTA Surakarta - Hafizh Firdaus; Hanafi Ridho A; Dewi Tafaul F; Latifah Khoirun N; Gybran Aldi A; Rara Intan Mutiara F (Pustaka Bangsa Indonesia, 2026)
Abstract Measurement, assessment, and evaluation are essential components in the learning process of Islamic Religious Education (IRE). These components function not only to determine students' learning achievement but also to improve the quality of instruction. This article aims to analyze the implementation of measurement, assessment, and evaluation in improving the quality of Islamic Religious Education learning at secondary schools. The study employed a literature review method by examining various scientific journals, books, and relevant research findings. The results indicate that measurement provides quantitative data regarding students' learning outcomes, assessment interprets the obtained data, and evaluation serves as a basis for decision-making regarding the effectiveness of learning activities. Effective implementation of these three components contributes to improving learning quality through instructional improvement, increasing student motivation, and developing cognitive, affective, and psychomotor competencies. However, several challenges remain, including the dominance of cognitive assessment, limited teacher competence in authentic assessment, and inadequate utilization of educational technology in evaluation practices. Therefore, comprehensive and sustainable evaluation systems are needed to support quality Islamic Religious Education learning in secondary schools. Keywords: Measurement; Assessment; Evaluation; Islamic Religious Education; Learning Quality Abstrak Pengukuran, penilaian, dan evaluasi merupakan komponen utama dalam pembelajaran Pendidikan Agama Islam (PAI) yang berperan dalam mengukur capaian belajar sekaligus meningkatkan kualitas pembelajaran. Penelitian ini bertujuan menganalisis implementasi pengukuran, penilaian, dan evaluasi dalam meningkatkan kualitas pembelajaran PAI di sekolah menengah. Penelitian menggunakan metode studi pustaka dengan mengkaji buku, artikel jurnal ilmiah, dan hasil penelitian yang relevan. Hasil kajian menunjukkan bahwa pengukuran menghasilkan data kuantitatif hasil belajar, penilaian memberikan makna terhadap data tersebut, sedangkan evaluasi menjadi dasar pengambilan keputusan untuk memperbaiki efektivitas pembelajaran. Implementasi ketiga komponen secara terpadu berkontribusi terhadap peningkatan kompetensi kognitif, afektif, dan psikomotorik peserta didik serta mendorong perbaikan proses pembelajaran secara berkelanjutan. Namun, penerapannya masih menghadapi kendala berupa dominasi penilaian kognitif, keterbatasan kompetensi guru dalam penilaian autentik, dan rendahnya pemanfaatan teknologi dalam evaluasi. Oleh karena itu, diperlukan sistem evaluasi yang komprehensif dan berkelanjutan. Kata kunci: Pengukuran; Penilaian; Evaluasi; Pendidikan Agama Islam; Kualitas Pembelajaran